Предмет: Математика,
автор: sisterssuper
0.6(-2y+3)-0.4(9-y)=-0.3(y-9)помогите решить уравнение
Ответы
Автор ответа:
0
0.6(-2y+3)-0.4(9-y)=-0.3(y-9)
-1.2y+1.8-3.6+0.4y=-0.3y+2.7
-0.8y-1.8=-0.3y+2.7
-0.8y+0.3y=2.7+1.8
-0.5y=4.5
y=4.5/(-0.5)
y=-9
-1.2y+1.8-3.6+0.4y=-0.3y+2.7
-0.8y-1.8=-0.3y+2.7
-0.8y+0.3y=2.7+1.8
-0.5y=4.5
y=4.5/(-0.5)
y=-9
Похожие вопросы
Предмет: Физика,
автор: Snake505
Предмет: Математика,
автор: yuav315
Предмет: История,
автор: Аноним
Предмет: Физика,
автор: ildarsol
Предмет: Алгебра,
автор: larinanatalia66